Knowledge Management and Role Clarity as Antecedents of Service Quality - Kankam Jr., George (British Journal of Marketing Studies, 2022)
The effective management of employees’ knowledge has been described as a critical ingredient for organisations seeking to ensure sustainable strategic competitive advantage in the market place. The purpose of the study was to investigate the impact of knowledge management on employees’ role clarity and quality of services. The study sampled 300 staff from three private hospitals in Ghana namely: Trust Hosiptal, Otoo Memorial Hospital and Cocoa Hospital. The purposive sampling technique was employed to select the private hospitals while simple random was used to select staff of the hosptials. The results revealed that service quality has a positive relationship on knowledge management and service quality